2015
DOI: 10.1016/j.actpsy.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Bridging music and speech rhythm: Rhythmic priming and audio–motor training affect speech perception

Abstract: Following findings that musical rhythmic priming enhances subsequent speech perception, we investigated whether rhythmic priming for spoken sentences can enhance phonological processing - the building blocks of speech - and whether audio-motor training enhances this effect. Participants heard a metrical prime followed by a sentence (with a matching/mismatching prosodic structure), for which they performed a phoneme detection task. Behavioural (RT) data was collected from two groups: one who received audio-moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 45 publications
8
77
0
4
Order By: Relevance
“…The design of the current study did not enable us to decide which aspect of language processing -lower-level auditory processing of phonemes and syllables, the processing of hierarchical linguistic structures or both -is facilitated by the regular prime, neither to explore the underlying mechanisms. The result that rhythmic priming facilitates phonological processing (Cason, Astésano, & Schön, 2015;Cason & Schön, 2012) supports the role of auditory processing, but future studies need to find out whether improved grammatical processing is accounted for by better auditory processing in itself or rhythmic priming facilitates both auditory processing and grammatical processing.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The design of the current study did not enable us to decide which aspect of language processing -lower-level auditory processing of phonemes and syllables, the processing of hierarchical linguistic structures or both -is facilitated by the regular prime, neither to explore the underlying mechanisms. The result that rhythmic priming facilitates phonological processing (Cason, Astésano, & Schön, 2015;Cason & Schön, 2012) supports the role of auditory processing, but future studies need to find out whether improved grammatical processing is accounted for by better auditory processing in itself or rhythmic priming facilitates both auditory processing and grammatical processing.…”
Section: Discussionmentioning
confidence: 93%
“…The effect was also found in young adults with and without dyslexia who showed a larger ERP response to grammatical violations following regular vs. the irregular primes . While most of the studies tested the effect of rhythmic priming on grammaticality judgment, a few works tested its effect on phonological perception in nonexistent words (Cason & Schön, 2012) and sentences (Cason, Astésano, & Schön, 2015). These studies used a slightly different priming paradigm from the grammaticality judgment studies as the rhythm of the primes either matched or did not match the prosodic structure of the speech stimuli.…”
Section: Rhythmic Primingmentioning
confidence: 99%
“…If sensitivity to linguistic beat-based temporal structure is impaired in developmental dyslexia, this would lead to phonological impairments. By TS theory therefore, beneficial effects of rhythmic tapping on phonological development and reading would occur via improved temporal precision of auditory oscillatory networks via coupling with motor oscillators (see also Putkinen et al, 2013; Cason et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The identification of underlying neural mechanisms would help to optimize remediation. Synchronizing to a beat is a complex process, requiring accurate internal time-keeping, the production of steady movements, and the use of auditory feedback to predict and correct the timing of action (Sowinski and Dalla Bella, 2013; Cason et al, 2015; Tierney and Kraus, 2016). To take the example of dyslexia, if the primary sensory impairment is auditory rather than motor, then rhythmic interventions involving a motor component (e.g., drumming) may improve rhythmic synchronization in affected children via sensorimotor coupling, with consequent effects on auditory and language processing driven by the motor practice (Goswami, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…
Previous research has shown that rhythmic training enhances phonological speech processing (e.g., [1,2,3,4]). Yet little is known about whether rhythmic training can also help to improve pronunciation in a second language (but see [5,6,7]).
…”
mentioning
confidence: 99%